FAKTOR-FAKTOR YANG MEMENGARUHI PENUNDAAN KELAHIRAN ANAK PERTAMA DI WILAYAH PERDESAAN INDONESIA: ANALISIS DATA SDKI 2012 - Risa Ruri Indraswari; Risni Julaeni Yuhan (Jurnal Kependudukan Indonesia, 2017)
A large number of population that not followed by the quality of human resources will burden the development of a country. Thus, some efforts are needed to reduce the fertility level. One solution to this issue is to delay the first birth. This study aims to assess the delayed first child birth in rural Indonesia and the affecting factors. This study analyzed secondary data using descriptive approach to have a general description of the delayed first birth. Moreover, a binary logistic regression model was fitted to determine the associated factors.Â  The results show that a socioeconomic variable that significantly associated with the delayed first child birth is husbandâ€™s job in the non-agricultural sector. Furthermore, the significant demographic variables are the age of first marriage age and the perception of an ideal number of children.